The relationship between parental overprotection and student depression: The chain mediation role of psychological control and well-being - Shuyu Huang (PLoS ONE, 2025)
This study investigated the relationship between parental overprotection and adolescent depressive symptoms, focusing on the chain mediation roles of psychological control and well-being. Using a survey-based design with a convenience sample of 823 adolescents aged 10–14, data were collected through validated scales measuring parental overprotection, psychological control, well-being, and depressive symptoms. Mediation analysis, conducted with the PROCESS macro for SPSS, revealed that parental overprotection exerts a significant positive effect on adolescent depression. Specifically, parental overprotection increases psychological control, which in turn reduces well-being, thereby exacerbating depressive symptoms. These findings underscore the importance of balanced parenting practices that limit psychological control and promote adolescent autonomy and well-being. Educators and mental health professionals are encouraged to collaborate with families to reduce overprotective behaviors and enhance adolescents’ resilience against depressive symptoms.